Stroop-like effects for monkeys and humans: processing speed or strength of association? - Washburn, David A. (Psychological Science., 1994)
A study was conducted to determine whether Stroop-like effects could be observed in the processing of numerical stimuli by rhesus monkeys. Six monkeys and 28 humans took part in a relative-numerousness task. The findings indicated that monkeys, like humans, processed the meanings of the numerical symbols automatically, despite the fact that these meanings bore no relevance to task performance. Relative to baseline, the performance of both humans and monkeys was significantly compromised by incongruent trials and significantly facilitated by congruent trials. These results were in accordance with parallel-processing models of Stroop-like interference proposed elsewhere. However, analysis of the effects of array-size difference in the relative-numerousness task did not support the speed-of-processing hypothesis that predicted that array differences of four to seven numerals would produce less interference and facilitation than would differences of one to three numerals.